Mainz and the middle Rhine Valley
1 online resource
Keywords: This book explores the medieval art, architecture, and archaeology of the city of Mainz and of the middle Rhine valley. It considers the architecture and archaeology of the early medieval and Romanesque period, including the Carolingian monastery of Lorsch and the cathedrals of Mainz and Worms.